Microglia centered pathogenesis in ALS: insights in cell interconnectivity - Brites, Dora; Vaz, Ana R. (Frontiers in Cellular Neuroscience, 2014)
Amyotrophic lateral sclerosis (ALS) is the most common and most aggressive form of adult motor neuron (MN) degeneration. The cause of the disease is still unknown, but some protein mutations have been linked to the pathological process. Loss of upper and lower MNs results in progressive muscle paralysis and ultimately death due to respiratory failure. Although initially thought to derive from the selective loss of MNs, the pathogenic concept of non-cell autonomous disease has come to the forefront for the contribution of glial cells in ALS, in particular microglia. Recent studies suggest that microglia may have a protective effect on MN in an early stage. Conversely, activated microglia contribute and enhance MN death by secreting neurotoxic factors, and impaired microglial function at the end-stage may instead accelerate disease progression. However, the nature of microglial-neuronal interactions that lead to MN degeneration remains elusive. We review the contribution of the neurodegenerative network in ALS pathology, with a special focus on each glial cell type from data obtained in the transgenic SOD1G93A rodents, the most widely used model. We further discuss the diverse roles of neuroinflammation and microglia phenotypes in the modulation of ALS pathology. We provide information on the processes associated with dysfunctional cell-cell communication and summarize findings on pathological cross-talk between neurons and astroglia, and neurons and microglia, as well as on the spread of pathogenic factors. We also highlight the relevance of neurovascular disruption and exosome trafficking to ALS pathology. The harmful and beneficial influences of NG2 cells, oligodendrocytes and Schwann cells will be discussed as well. Insights into the complex intercellular perturbations underlying ALS, including target identification, will enhance our efforts to develop effective therapeutic approaches for preventing or reversing symptomatic progression of this devastating disease.